Contract for Services between the MasterCard Foundation and BRAC Development Institute of BRAC University and BRAC, USA (2012) - Master Card Foundation; BDI, BRAC University; BRAC, Usa (The MasterCard Foundation and BDI, BRAC University and BRAC, USA, 2013)
1. Background Information. 2. Services and Consideration. 3. Term and Termination. 4. Confidentiality, Privacy, Anti-Terrorism. 5. Intellectual Property. 6. General Provisions.